(untitled) (Medico Legal Update, 2020)
In the world 9.4 million people have been infected with TB disease and each year 1.7 million people die (WHO, 2013). The risk of lung TB increased in patients with DM as a defect in immune cell function and defence mechanism. In addition, it is also determined by the reduced leukocytes in patients with DM, especially for those whose sugar levels are not controlled. The purpose of research is to analyze the duration of DM, contact with TB and BMI on the occurrence of lung TB in patients with DM. Research conducted at the Puskesmas Glugur Darat, Puskesmas Sering and Puskesmas Padang Bulan Selayang in Medan City with a case-control study design. The population of the case is all patients DM with a lung TB recorded in Puskesmas and control is all patients with DM without lung TB. Samples taken with consecutive those are patients with DM who came to the puskesmas during the research until obtained 54 cases and 54 control. Data is analyzed by chi-square test and OR measuring. The results showed that there was influence of contact history of DM sufferers on the incidence of lung TB with OR = 4.38 (95% CI: 1.34-14.33) and BMI with OR = 3.5 (95% CI: 1.52-8.06).